DISCOURSE AND THE READER (International journal of artificial intelligence, 2025)
The interaction between discourse and the reader plays a crucial role in the formation of meaning within any written or spoken text. Discourse is more than a collection of words or sentences; it is a structured and purposeful unit shaped by linguistic, social, and cultural factors. The reader, in turn, actively constructs meaning by interpreting language through personal experience, background knowledge, and contextual understanding. This article explores how readers interpret discourse, the importance of coherence and cohesion, the influence of context, and the ways discourse awareness can improve academic reading and communicative competence.